Dendritic cell-based vaccine research against cancer. (February 2014) - Mody, Nishi; Dubey, Surbhi; Sharma, Rajeev; Agrawal, Udita; Vyas, Suresh P
<x xml:space="preserve">Abstract</x> Therapeutic vaccines that treat cancers with the help of the patient's own immune system signify a feasible option for active immunotherapy against the disease. Dendritic cells (DCs) play a central role in modulating the immune response and thus can be wisely utilized as an immunotherapeutic strategy for cancer regimens. Advances in the knowledge of DC biology and function have led to the development of DC-based vaccines for cancer therapy. In the present review, we discuss the biology and function of DCs, their subsets and receptors, antigen loading and route of administration of DC vaccines, as well as active and passive targeting strategies for treating the cancer. We also discuss the preclinical and clinical status of these newly developed vaccines. Special attention should be given by the scientific community to the challenges that need to be solved for the successful implication of these vaccines in cancer therapy.